SYNTHESIS AND STUDY OF THE PROPERTIES OF BIS-CARBAMATE MEE-2 AND ITS DERIVATIVES - Mashaev , Eldor; Azamatov , Utkirbek; Jo‘raqulov , Sherbek (Educational Research in Universal Sciences, 2024)
This scientific work discusses synthesis methods and development of waste-free, energy-saving, environmentally friendly and resource-saving technology for the production of N, N’-hexamethylene bis [(m-cresol)-carbamate], i.e. MEE-2 and its derivatives. And also, the study of the N-H center of the MEE-2 molecule where the chemical transformation occurs according to the mechanism of SN nucleophilic addition. As a result, a new, previously little studied area of chemistry of bis-carbamate compounds based on cresol and hexamethylene diisocyanate has emerged.